2002
DOI: 10.1017/s0047279402006761
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Sex Education Policy in England and Wales and The Netherlands since the 1980s

Abstract: Teenage pregnancy rates are extremely high in the UK and extremely low in The Netherlands. Sex education is acknowledged to be a determining factor. While it is by no means the most important factor, it provides a useful comparative lens through which to examine the very different approaches of the British and Dutch to policy-making in this sensitive area.The issue of sex education is controversial in both the UK and The Netherlands, but while the political debate has been fierce in the UK it has been l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 17 publications
1
29
0
1
Order By: Relevance
“…Allen and Bourke Dowling (1999), in their UK study, focus on the way teenage mothers are seen as burdens on the state, and quote research by Hudson and Ineichen (1991) that indicates how most young women do not make a positive choice to become pregnant as part of a welfare plan to obtain bene ts. Lewis (2002) looked at the UK gures in relation to the lower conception rates in the Netherlands and concluded that it was both the presence of a social consensus around sexual relationships that was supported by a strong church in uence and the way sexual desire, especially in the young, was not politicised. She, too, makes the point that solutions cannot work except within the prevailing social rules.…”
Section: Policy Discoursesupporting
confidence: 56%
“…Allen and Bourke Dowling (1999), in their UK study, focus on the way teenage mothers are seen as burdens on the state, and quote research by Hudson and Ineichen (1991) that indicates how most young women do not make a positive choice to become pregnant as part of a welfare plan to obtain bene ts. Lewis (2002) looked at the UK gures in relation to the lower conception rates in the Netherlands and concluded that it was both the presence of a social consensus around sexual relationships that was supported by a strong church in uence and the way sexual desire, especially in the young, was not politicised. She, too, makes the point that solutions cannot work except within the prevailing social rules.…”
Section: Policy Discoursesupporting
confidence: 56%
“…European sex education is evaluated as being of high quality (Beaumont and Maguire 2013) and the Netherlands especially is regarded a front runner (Lewis and Knijn 2002;Weaver, Smith, and Kippax 2005). Since 1993, schools are obliged to offer sex education on different topics, although schools may decide for themselves how much time they spend on this work, as well as which approach, methods and materials they use (Weaver, Smith, and Kippax 2005, 174).…”
Section: Introductionmentioning
confidence: 99%
“…This positive, empowering approach is remarkable in comparison to other countries, including European countries such as the UK, where debates about sex education are sometimes dominated by more conservative moral views (Lewis and Knijn 2002). Indeed, the Dutch Government states that the central aim of sex education is to empower young people by providing them with sexual knowledge so that later they can 'take their own responsibility' for building 'consensual, safe, and pleasurable sexual relations' (Bussemaker 2009, 3, 7-8;Schippers 2011, 53).…”
Section: Introductionmentioning
confidence: 99%
“…National policy requires that secondary school students learn about contraceptives and condom use, identity formation, social skills and sexual diversity. The 'Dutch approach' (Lewis and Knijn 2002;Senanayake, Nott, and Faulkner 2001) has been characterized as pioneering and successful in preventing sexual transmittable diseases (STDs) and teenage pregnancies. As a result, the Netherlands have been praised as having achieved the status of a guiding country for the prevention of teenage pregnancies (Harbers 2006), and its sex education became a successful export product (ZonMW 2012).…”
Section: Introductionmentioning
confidence: 99%